The Influence of Work Environment and Career Development on Employee Retention at Golden Tulip Jineng Resort Bali - Dhari, Anak Agung Ayu Tantri Pradnyan; Sulistyawati, Ni Luh Ketut Sri; Sabudi, Nyoman Sukana (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Decreasing Employee Retention can be a problem for companies that show an increase in employee turnover. Factors influencing employee retention are career development and creating a conducive work environment. The purpose of this study was to determine how the work environment and career development impact employee retention at GT Jineng Resort Bali. All employees of GT Jineng Resort Bali were 64 sample respondents using saturated sampling techniques. The data analysis techniques used were multiple linear regression, coefficient of determination, tt test and F test. The results explain that the work environment and career development have a positive and significant effect on employee retention partially and simultaneously. The work environment and career development variables have an influence of 58.9% on employee retention. Researchers suggest that GT Jineng Resort Bali rearrange the work space, always be fair in giving promotions and always listen to every employee's career aspirations.